Radio and Electronics Cookbook - Brown, George (Radio Society of Great Britain, 2012)
The RSGB Radio and Electronics Cookbook is a unique collection of electronics projects, ideal for all electronics enthusiasts and experimenters. The simple step-by-step instructions also make this book ideal for amateurs seeking to build up their electronics skills and knowledge.